Involvement of GOBP2 in the perception of a sex pheromone component in both larval and adult Spodoptera litura revealed using CRISPR/Cas9 mutagenesis. (February 2022) - Han, Wei-Kang; Yang, Yi-Lin; Si, Yu-Xiao; Wei, Zhi-Qiang; Liu, Si-Ruo; Liu, Xiao-Long; Yan, Qi; Dong, Shuang-Lin
Abstract: General odorant-binding proteins (GOBPs) are long considered responsible for the perception of plant odorants. In this study with the important noctuid pest Spodoptera litura, we functionally characterized that GOBP2 is also involved in the perception of sex pheromone components using in vivo CRISPR/Cas9 technique. First, the GOBP2 sgRNA and Cas9 protein were injected into the newly laid insect eggs, resulting in a 35.6% target mutagenesis in G0 moths. Then, the homozygous GOBP2 knockout strain ( GOBP2 −/− ) was obtained after the screening of three generations. The knockout male and female moths displayed a significant reduction in EAG responses to the sex pheromone components, and the knockout females also displayed a significant reduction to plant odorants. In the behavioral assay of food choice, GOBP2 −/− larvae lost the preference to artificial diet added with the major sex pheromone component Z9, E11-tetradecadienyl acetate (Z9, E11-14:Ac), whereas the WT larvae highly preferred the pheromone diet. Y-tube olfactometer assay and direct pheromone stimulation assay showed that GOBP2 −/− male adults reduced significantly than WT males in percentages of choice, hair pencil displaying and mating attempt to Z9, E11-14:Ac. In the oviposition test, GOBP2 −/− females showed significantly reduced preference for the soybean plants compared to the WT females. Our study demonstrated that GOBP2 plays an important role in perceiving sex pheromones in adult and larval stages, providing new insight into sex pheromone perception and a potential target for sex pheromone-based behavioral regulation in the pest. Graphical abstract: Image 1 Highlights: GOBP2 mediates pheromone-guided food preference in Spodoptera litura larvae. GOBP2 −/− moths show reduced EAG response to sex pheromone components and host plant leaves. GOBP2 −/− male adults show reduced behavioral response to a pheromone component Z9, E11-14:Ac. GOBP2 −/− female adults show reduced oviposition preference to host plants.